A new speed adaptive estimation method based on an improved flux sliding-mode observer for the sensorless control of PMSM drives. (September 2022) - Wang, Guoqiang; Zhang, Huilin
Abstract: In this paper, an improved speed adaptive flux sliding-mode observer (FSMO) is presented for the sensorless control of surface-mounted permanent magnet synchronous motor (PMSM) drives. First, to suppress the chattering of the traditional FSMO, an algorithm for online adjusting the observer gain is designed. In this algorithm, a transition mode is introduced between the existing reaching and sliding modes, and an error criterion function with speed and current is constructed for the three motion modes. Second, to reduce the rotor speed estimation error, a new speed adaptive estimation method is presented instead of the traditional phase-locked loop (PLL). In this method, the adaptive law for estimating the speed is derived using Lyapunov stability and model reference adaptive theories. Meanwhile, the physical meaning of the speed adaptive law is illustrated. Finally, the proposed FSMO scheme is implemented on a TMS320F28335 digital signal processing (DSP) microcontroller-based surface-mounted PMSM sensorless control experimental bench. Test results demonstrate the excellent dynamic performance, robustness and stability of the proposed FSMO under various operating conditions. Highlights: The PMSM sensorless control based on the traditional FSMO suffers from chattering problem. The use of traditional PLL to calculate rotor speed can reduce the observation performance of the system. A transition mode is proposed between the two motion modes of the sliding-mode control. An online gain adjustment algorithm based three motion modes is designed to suppress chattering. A new speed adaptive estimation method is presented to reduce the rotor speed estimation error.